Alcohol use predicts elevation in inflammatory marker soluble CD14 in men living with HIV. Issue 11 (1st November 2016) - Monnig, Mollie A.; Kahler, Christopher W.; Cioe, Patricia A.; Tucker, Lynne; Monti, Peter M.; Mayer, Kenneth H.; Ramratnam, Bharat
ABSTRACT: Independently, HIV infection and heavy alcohol use increase microbial translocation (MT) of gut products into systemic circulation. MT and consequent immune response have been linked to chronic inflammation and a host of negative health outcomes in individuals living with HIV. However, previous research has not systematically investigated the immune correlates of heavy drinking specifically within the HIV-positive population. This pilot study investigated MT and immune activation as a function of alcohol use in 21 HIV-positive men who met NIAAA criteria for heavy drinking. Participants averaged 46.7 ± 8.5 (mean ± standard deviation) years of age, 12.2 ± 9.2 years since HIV diagnosis, 337 ± 158 CD4 nadir, and 643 ± 245 current CD4 count. All participants were virologically suppressed on antiretroviral therapy. Data on alcohol use and immune function were collected at baseline and three-month follow-up. Plasma concentrations of markers of MT and immune activation (lipopolysaccharide (LPS), soluble CD14 (sCD14), endotoxin core antibody immunoglobulin M (EndoCAb)) were measured using enzyme-linked immunosorbent assays. Generalized estimating equation models tested alcohol use variables as predictors of LPS, sCD14, and EndoCAb levels. Greater quantity and frequency of drinking significantly predicted higher sCD14 levels ( p 's < .01). Conversely, longer duration of abstinence from alcohol significantly predicted lower sCD14 levels ( p  < .001). These results remained significant after controlling for age, HIV duration, smoking status, current CD4 count, CD4 nadir, and antiretroviral drug type. In addition, participants with ≥50% relative reduction in drinks per week showed a significant decrease ( p  < .05) in sCD14 from baseline to three-month follow-up. This pilot study provides preliminary evidence that heavy drinking may increase a key inflammatory marker in HIV-infected individuals with suppressed infection.